Canada's 150-minute 'standard' in physical education: a consideration of research evidence related to physical education instructional time. Issue 3 (2nd September 2019) - Robinson, Daniel B.; Randall, Lynn; Gleddie, Douglas L.; Barrett, Joe; Berg, Stephen
ABSTRACT: Though physical education instructional time varies across Canada, an idealised standard of 150 minutes per week has been identified, followed, and aspired to by many. For example, Canada's 'best performers' with respect to physical education instructional time achieve 150 minutes of weekly instruction. Moreover, Canada's national association for physical and health education supports this same benchmark, offering awards to schools that achieve it. However, while this standard exists in practice for some and as a goal for others, it exists without any notable or significant evidence underpinning the proposed standard. Consequently, the 150-minute standard seems to be a target number lacking substantiation. Given these observations, the purpose of the study was twofold. First, we aimed to conduct a scoping literature review so that it might be possible for one to more clearly rationalise this 150-minute position suggested by many. Second, within the sourced body of evidence, we sought to identify and describe what relationship, if any, exists between instructional time (particularly 150 minutes of instructional time) and familiar physical education-related variables (i.e. physical fitness, physical activity, movement competence, movement confidence, academic learning/readiness). Considering our findings from this literature review, we also offer insights and possibilities for future inquiry, practice, and advocacy.